2003
DOI: 10.1046/j.1525-1438.2003.13197.x
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic insight on in vivo expression of interleukin-6 in uterine cervical cancer

Abstract: Interleukin-6 (IL-6) is a multifunctional cytokine with a growth promoting role in cancers. In an attempt to evaluate the prognostic significance of IL-6, we have studied the localization of this cytokine by immunohistochemical methods in normal, premalignant, and invasive cervical cancers. We stained frozen sections with a monoclonal antibody specific for human IL-6 and demonstrated that tumor cells show positivity with high intensity and stromal cells with moderate intensity. T cells and macrophages, compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Of note, we and other groups have previously shown that IL-6 and M-CSF are highly upregulated in human cervical carcinogenesis in situ (26,27). IL-6 has been correlated with a negative prognosis in these patients (36). Cervical cancer cells hardly responded to IL-6, and this suggested a paracrine role for IL-6 (27).…”
Section: Discussionmentioning
confidence: 61%
“…Of note, we and other groups have previously shown that IL-6 and M-CSF are highly upregulated in human cervical carcinogenesis in situ (26,27). IL-6 has been correlated with a negative prognosis in these patients (36). Cervical cancer cells hardly responded to IL-6, and this suggested a paracrine role for IL-6 (27).…”
Section: Discussionmentioning
confidence: 61%
“…It is well-known that host immune response and chronic inflammation play critical roles on preventing the progression of cervical cancer (Shi et al, 2013). IL-6, an important pro-inflammatory cytokine, is a multifunctional protein principally involved in the genesis and maintenance of the inflammatory response (Kyo et al, 2000;Srivani et al, 2003;Shi et al, 2013). There is local production of IL-6 in cervicovaginal secretions.…”
Section: Discussionmentioning
confidence: 99%
“…IL6 has a negative impact on the prognosis of a patient (16). We have shown that it mainly acts in a paracrine manner and creates a protumorigenic and immunosuppressive microenvironment (10,17,18).…”
Section: Introductionmentioning
confidence: 93%